Determinants of Online Loan Adoption among Gen Z’s: The Role of Gender, Financial Literacy, Self-Efficacy, and Risk Perception - Jannata, Putrila Maya; Suhartini, Dwi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates how gender, financial literacy, financial self-efficacy, and risk perception influence the intention to use online lending services among Generation Z university students in Surabaya. Methodology: A quantitative approach was applied using Partial Least Squares-SEM (SmartPLS 4.0) on a sample of 290 accounting students, selected through stratified random sampling. Data were collected via online surveys. Findings: Financial literacy and self-efficacy significantly and positively influence online loan interest, while perceived risk shows a significant negative impact. Gender was not found to be a significant factor. Novelty: This research contributes to the fintech behavioral literature by confirming the dominance of cognitive and psychological drivers over demographic characteristics in shaping Gen Z’s online loan interest. Originality: The study adds a regional context by focusing on accounting students in Surabaya, representing a tech-savvy and financially literate cohort, with gender explored as a non-significant differentiator. Conclusion: Online loan interest is primarily shaped by internal competencies (literacy, self-efficacy) and risk aversion rather than demographic traits like gender. Type of Paper: Research Article.